Product Development Drivers: An Explorative Study in Finland and China - Jukka Majava; Kris M. Y. Law; Harri Haapasalo; Y. C. Chau; Osmo Kauppila (International School for Social and Business Studies, 2018)
New Product Development (NPD) is vital for companies that operate in international markets. Yet, NPD has become increasingly challenging to manage; products are becoming ever more complex and various customers and multiple stakeholders' needs must be satisfied. Additionally, NPD is often conducted in multiple locations around the world. Product development drivers can be defined as reasons for a company to initiate a product development project. These drivers affect decision-making, project outcome, and product strategy implementation. This study explores how product development drivers are perceived at the managerial level in technology companies based in Finland and China. The results indicate that managers' views on these drivers differ in short-, medium-, and long-term development projects. Marketing and customers related drivers are considered the most important in the short term; financial goals related drivers in the medium term, and strategy and business environment related drivers in the long term. Furthermore, differences are found between Finnish and Chinese managers' views. Finnish practitioners tend to be more focused on financial goals related drivers, whereas Chinese managers consider various factors important.